ChemInform Abstract: A Simple and Efficient Tetradentate Schiff Base Derived Palladium Complex for Suzuki—Miyaura Reaction in Water. Issue 32 (24th July 2014) - Dewan, Anindita; Bora, Utpal; Borah, Geetika
Abstract A simple catalytic system based on a Pd‐complex of a tetradentate Schiff base promotes the Suzuki—Miyaura cross‐coupling reaction of aryl bromides in water as the solvent.